Qur’anic Exegesis in the Digital Era: Mapping Fiqh Discourses on NU Online during the 2023–2024 Period - Nur Muhamad Iskandar; Izzah Faizah Siti Rusydati Khaerani (Khazanah Theologia, 2024)
Purpose: This study aims to map the systematics of writing, modes of presentation, and exegetical topics on NU Online during the 2023–2024 period, while also examining exegetical tendencies in responding to contemporary religious and social issues. The research seeks to understand how digital Qur’anic interpretation reflects the interaction between sacred texts and current social dynamics within Indonesia’s largest Islamic organization. Methodology: The research employs a qualitative method with a content analysis approach applied to 274 exegetical articles published on NU Online. The data were systematically analysed through thematic categorization and coding to identify patterns in writing systematics (mushafī and thematic), exegetical approaches (textual and contextual), and thematic tendencies emerging from the corpus. Findings: The findings highlight two major patterns. First, fiqh-oriented interpretation dominates NU Online’s exegesis, particularly in discussions concerning ritual law (ʿibādah) and social transactions (muʿāmalah). Second, the exegesis tends to engage socio-political issues using an accessible, popular style while promoting values of social empowerment and moderation. Research Implications: The study underscores that digital media functions not merely as a channel for reproducing religious knowledge, but as a dynamic site of dialectic between the Qur’anic message and the needs of the Muslim community. It further highlights the potential of digital platforms as spaces for contextualising Islamic scholarship in public discourse. Originality/Value: This research contributes to the growing field of digital Qur’anic studies by offering a systematic mapping of NU Online’s digital exegesis. It highlights the centrality of fiqh as a dominant interpretive framework in addressing contemporary challenges and demonstrates how traditional Islamic reasoning adapts within the digital sphere.